The way teachers visualize science material is related to the quality of students' understanding: cara guru mengvisualisasi materi sains kaitanya dengan kualias pemahaman siswa - Dahlia, Siti (SEARCH: Science Education Research Journal, 2025)
Education is one way of supporting the quality of human resources through the learning process (Nurinda and Kasman, 2021). In an effort to improve the quality of education, every educational institution must create an effective and efficient learning process (Ardiansyah et al., 2019). Therefore, learning is a learning process that has been designed, systematic, and has a formal nature, and is held by an educational institution (Prawiyogi et al 2020). According to Novantara (2017), effective and efficient learning activities are characterized by achieving previously formulated learning objectives. The type of research used in this research is qualitative research because the data collected comes from the opinions of the target subjects. The technique for collecting data used was an interview with one of the teachers at MI Emyodere, Sorong City, Southwest Papua, to draw conclusions and record data. The aim of this research is of course to investigate the effect of the visualization methods used by teachers in teaching science materials on improving the quality of students' understanding. This research aims to provide deeper insight into effective pursuit strategies in the context of science learning. Population is the overall object of research. The population in this research is teachers at MI Emeyodere, Sorong City, Southwest Papua. The sample is part of the total population. The sample in this study was MI Emeyodere class VI, including 20 students. The curriculum in Indonesia is always developing and from time to time the development of this curriculum is based on the demands of the millennial era. Science learning in question is the way teachers visualize science material. In this case, it is learning where the teacher plays an important role in developing visualizations of science material to improve understanding. students at MI Emeyodere, Sorong City. Science learning not only teaches mastery of facts, concepts and principles about nature but also teaches methods of solving problems, trains critical thinking skills and draws conclusions, trains being objective, working together and respecting other people's opinions. Learning media is a means of the process of conveying learning information from teachers to students. Material or messages can be conveyed through several types of media, one of which is visual media. Visual media is media that is enjoyed by the sense of sight. The use of visual media can facilitate students' understanding. The science learning process for students at MI Emeyodere, Sorong City using visualization of science material can improve students' understanding. because students easily grasp the learning material delivered by the teacher quickly.